2011
DOI: 10.1002/hed.21890
|View full text |Cite
|
Sign up to set email alerts
|

Plasma epstein‐barr virus DNA concentration and clearance rate as novel prognostic factors for metastatic nasopharyngeal carcinoma

Abstract: The pretreatment plasma EBV DNA copy number and their clearance rates are significant predictors for NPC treatment outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
53
1
7

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(66 citation statements)
references
References 23 publications
3
53
1
7
Order By: Relevance
“…EBV-DNA may be detected in NPC cells (5,6), and cell-free EBV-DNA may be detected in the plasma of patients with NPC (7)(8)(9)(10)(11)(12)(13). Furthermore, the levels of plasma EBV-DNA in recently diagnosed NPC patients have been significantly correlated with tumor volume (14,15), response to treatment (16), tumor clearance (17,18) and tumor recurrence (19)(20)(21). Similarly, it has been observed that a positive post-treatment detection of plasma EBV-DNA is predictive of poor outcomes in terms of subsequent relapse rate, overall survival (OS) and relapse-free survival (RFS) (11,13).…”
Section: Introductionmentioning
confidence: 99%
“…EBV-DNA may be detected in NPC cells (5,6), and cell-free EBV-DNA may be detected in the plasma of patients with NPC (7)(8)(9)(10)(11)(12)(13). Furthermore, the levels of plasma EBV-DNA in recently diagnosed NPC patients have been significantly correlated with tumor volume (14,15), response to treatment (16), tumor clearance (17,18) and tumor recurrence (19)(20)(21). Similarly, it has been observed that a positive post-treatment detection of plasma EBV-DNA is predictive of poor outcomes in terms of subsequent relapse rate, overall survival (OS) and relapse-free survival (RFS) (11,13).…”
Section: Introductionmentioning
confidence: 99%
“…The meta-analysis found that high pre-treatment levels of EBV DNA had good value as a prognostic indicator of survival and disease outcomes in patients with NPC. Most of the studies included in this meta-analysis found that increased levels of EBV DNA prior to treatment was associated with poor overall survival [13,[28][29][30][32][33][34][35][36][37]39,40]. Of the studies that evaluated the other outcomes, high pre-treatment EBV DNA levels was also associated with increased risk for disease progression, relapse, recurrence, and distant metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…The remaining 57 were fully evaluated for inclusion and 41 were eliminated for not reporting the outcomes of interest, reporting data that could not be pooled for a meta-analysis, not being relevant or reporting findings from a study that was already included. Sixteen studies were included in the study with a total of 7698 patients [12,13,[28][29][30][31][32][33][34][35][36][37][38][39][40][41]. Three of the studies were retrospective in design and the remaining 13 studies were prospective (Table 1).…”
Section: Literature Searchmentioning
confidence: 99%
“…The drop in viral DNA in the blood during RT/CHRT was accompanied by remission of NPC as a response to treatment [21]. Patients with more rapid clearance of EBV DNA from the circulation responded better to treatment and had a better survival probability [22,23]. Due to high sensitivity and specificity [24,25], plasma EBV DNA has been adopted as a marker for clinical management of patients with NPC [26].…”
Section: Discussionmentioning
confidence: 99%